Oxygenation during hypothermic rat liver preservation: an in vitro slice study to demonstrate beneficial or toxic oxygenation effects. - 't Hart, N; van der Plaats, A; Faber, A; Leuvenink, H; Olinga, P; Wiersema-Buist, J; Verkerke, G; Rakhorst, G; Ploeg, R (2005)
Hypothermic machine perfusion (HMP) of abdominal organs is shown to be superior compared to cold storage. However, the question remains if oxygenation is required during preservation as oxygen is essential for energy resynthesis but also generates toxic reactive oxygen species (ROS). To determine if oxygenation should be used during HMP, urea-synthesis rate, adenosine triphosphate (ATP), and generation of ROS were studied in an in vitro model, modeling ischemia-reperfusion injury. Furthermore, expression of uncoupling protein-2 (UCP-2) mRNA was assessed since UCP-2 is a potentially protective protein against ROS. Rat liver slices were preserved for 0, 24, and 48 hr in University of Wisconsin machine perfusion solution (UW-MP) with 0%, 21%, or 95% oxygen at 0-4 degrees C and reperfused for 24 hours. In the 0% and 95% groups, an increase of ROS was found after cold storage in UW-MP. After slice reperfusion, only the 0% oxygen group showed higher levels. The 0% group showed a lower urea-synthesis rate as well as lower ATP levels. mRNA upregulation of UCP-2 was, in contrast to kidney mRNA studies, not observed. In conclusion, oxygenation of UW-MP gave better results. This study also shows that ROS formation occurs during hypothermic preservation and the liver is not protected by UCP-2. We conclude that saturation of UW-MP with 21% oxygen allows optimal preservation results.